مشكلة الشعور بالعزلة الاجتماعية لدى المسنين: دراسة ميدانية في إرشاد المسنين - زغير، اكرام دحام (رابطة التربويين العرب, 2017)
إن المسنين يعانون من عدم الاهتمام بحالتهم الصحية والنفسية والاجتماعية وإن ما يتوفر لهم في المجالات المعنية وأنشطة مختلفة ومتعددة لكن بشكل محدود مما يولد لديهم الشعور بالعزلة والحدة ترتبط والقصور والعجز في الاتصال بالآخرين وإقامة العلاقات معهم إذ تتسم العلاقات الاجتماعية في ظل العزلة بالسطحية مع الشعور باليأس والنبذ ويحس الفرد الذي يشعر بالوحدة أو العزلة أنه بعيد عن الآخرين وأنهم لا يقبلون به ولا يشبعون له حاجاته الاجتماعية في الاتصال بهم وقصور في العلاقات الاجتماعية التي يقيمها معهم، يهدف البحث الحالي إلى التعرف على: مستوى الشعور بالعزلة الاجتماعية لدى المسنين. ودلالة الفروق في مستوى الشعور بالغزلة الاجتماعية لدى المسنين حسب متغير الجنس (ذكور – إناث). اختيرت عينة عشوائية بسيطة من المسنين المتواجدين في دار رعاية المسنين الصليخ وبلغ عددهم (25) مسن ومسنة موزعين بواقع (14) من الذكور، و(11) من الإناث وباستخدام مقياس العزلة لقياس لدى المسنين، ظهر من خلال النتائج التي تم التوصل إليها ما يلي: إن هنالك شعور بالعزلة لدى المسنين. لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) بين المسنين وفقا لمتغير الجنس. الاستنتاجات: في ضوء نتائج البحث يمكن استنتاج ما يلي: يعاني المسنون بشكل من العزلة الاجتماعية على اختلاف مستوياتهم حيث قد يكون المسن موظف أو يعمل أو متقاعد قبل أن يدخل الدار مما جعله يشعر بالعزلة الاجتماعية. أن عامل الجنس (الذكور – الإناث) كليهما يشعرون بالعزلة الاجتماعية لأنهم يعيشون في نفس الدار وآرائهم وأفكارهم متقاربة. التوصيات: وفقا لم توصل البحث إليه من نتائج نوصي بما يلي: توفير خدمة المختص الاجتماعي باستخدام الهاتف ليتسنى للمسنين التواصل معه. وتنظيم برامج ثقافية وترويحية للمسنين لتمتين التواصل الاجتماعي لديهم والحد من الشعور بالعزلة الاجتماعية. المقترحات: استكمالا للبحث الحالي وتطويرا له نقترح أجراء البحوث الآتية: أجراء دراسة بناء برنامج لإرشاد المسنين لخفض مستوى الشعور بالعزلة الاجتماعية لدى المسنين.
That older people suffer from lack of attention to health, psychological and social their case, and that what is available to them in the areas concerned and the activities of many different but in a limited way, which generates their sense of isolation and unity are linked, palaces and the deficit in contact with others and establish relationships with them as characterized by social relations under isolation superficiality with a sense of despair and ostracism and feel of the individual who feels lonely and isolated that he is far from the others and they do not them towards him in any way because of the weakness in contact with accept it and be satisfied his various social needs as it fails to attract accept it and be satisfied his various social needs as it fails to attract them and a lack of social relationships held by them, aimed current search to identify :The level of sense of social isolation among the elderly The significance of differences in the level of a sense of social isolation among the elderly by Mngaragans (Zkor- females Chosen a simple random sample of elderly people who are in nursing home Suleikh and numbered (25) elderly and elderly distributors by 14 males and 11 females, and using the isolation measure of the measure in the elderly, demonstrated by the results that have been reached following an There is a feeling of isolation among the elderly .latojd statistically significant differences at the level of (0.05) among the elderly, according to gender In light of the search results it can be concluded the following iena elderly people in general of social isolation indicators at all levels where it may be an officer of the elderly or working or retired before he enters the house, making it feel social is olationan sex worke (Zkor- females) both feel social isolation because they live in the same house and their ideas and opinions close According to the results of research came out with some recommendations including bina a pilot program to reduce the level of Alhaourbaezzlh in the elderly. taufer internet service for the elderly in order to communicate with others And a development of the current search proposed holding the following research. The level of sense of social isolation among the elderly depending on other variables (such as attainment, marital status, age A study program to guide the elderly to reduce the level of feeling of social isolation among the elderly.
Keywords: العزلة الاجتماعية -- الاضطرابات النفسية -- الرعاية الاجتماعية -- الارشاد الاجتماعى -- كبار السن